Difluoromethylcarbene for iron-catalyzed cyclopropanation. Issue 27 (20th March 2017) - Duan, Yaya; Lin, Jin-Hong; Xiao, Ji-Chang; Gu, Yu-Cheng
Abstract : Fe-Catalyzed cyclopropanation of olefins with difluoromethylcarbene generated from sulfonium ylide Ph2 S + –CH − CF2 H with high diastereoselectivity is described. Abstract : Difluoroethylsulfonium salt, Ph2 S + CH2 CF2 H OTf −, was developed into a convenient difluoromethylcarbene reagent for the iron-catalyzed cyclopropanation of terminal olefins, giving various difluoromethyl–cyclopropanes with excellent diastereoselectivities and in high yields.